THE CINEMATIC OTHERING OF SITTING BULL IN THE ADAPTATION OF BURY MY HEART AT WOUNDED KNEE - Nurcahyo, Rachmat; Hapsarani, Dhita; Budianta, Melani; Kristianto, Bayu (UI Scholars Hub, 2023)
The marginalization of particular groups or people as a result of the idea that one group or person is better than another is known as the